Global perspectives on victimization analysis and prevention - Ayodele, Johnson Oluwole (Advances in criminology, victimology, serial violence, and the deep web (ACVSVDW) book series, 2020)
"This book examines the global picture of victimization and the culture of crime control and prevention"--